Persistence of Phrenic Nerve Palsy Following 28‐mm Cryoballoon Ablation: A Four‐Year Single Center Experience. Issue 7 (27th April 2015) - SAITOH, YUKIO; IRFAN, GHAZALA; CICONTE, GIUSEPPE; MUGNAI, GIACOMO; SIEIRA, JUAN; DI GIOVANNI, GIACOMO; BALTOGIANNIS, GIANNIS; CONTE, GIULIO; HÜNÜK, BURAK; STRÖKER, ERWIN; VELAGIĆ, VEDRAN; OVEREINDER, INGRID; et al.
<x xml:space="preserve">Abstract</x> Background Phrenic nerve palsy (PNP) is the most frequently observed complication in the setting of cryoballoon (CB) ablation (Arctic Front, Medtronic Inc., Minneapolis, MN, USA). Although, usually transient, resolving before the end of the procedure, persistent PNP (not resolving before the end of procedure) can occur. Literature on persistent PNP after second generation CB ablation is relatively sparse. Methods A total of 316 consecutive patients having undergone large 28‐mm CB ablation as index procedure in the Heart Rhythm Management Center, UZ Brussels, Belgium, from January 2009 to December 2013 were retrospectively reviewed for the study. Of these 117 patients were treated with the first generation CB (CB1) and 199 patients with the second generation CB (CB2). Results PNP occurred in 10% of the total population. Persistent PNP was only observed following CB2 ablation which occurred in 4.5% of the group. At a mean follow‐up of 11 months, diaphragmatic contraction in persistent PNP patients resumed in 78% (7/9) of the patients. In a final follow‐up at 5 and 20 months, PNP persisted in two patients, respectively. PNP during ablation in the right inferior pulmonary vein was only observed in the CB2 group. No predictors of persistency of PNP were observed. Conclusion Persistence of PNP only occurred in the CB2 group in 4.5% of patients. The majority of patients with persistent PNP were asymptomatic. In most of the patients having persistent PNP after ablation, complete phrenic nerve function resumed during follow‐up (78%).